Blended Learning in Saudi Higher Education Framework, Implications, and limitations - Alharbi, Samar (Advances in Social Sciences Research Journal, 2021)
In the modern era of teaching and learning, the education system witnessed many changes. New methods of teaching and learning are utilised in order to adapt to the growth of technology. Teachers used some teaching methods, such as online teaching, face to face teaching or a combination of both online and face to face known as blended learning (BL) environment. BL has been proven its advantages empirically in many studies. One of the significant advantages is that BL is used as an extended learning environment to reinforce knowledge and make learning more accessible by utilising technology and online resources. However, there are some drawbacks of implementing blended learning, such as the demand of time and teachers’ efforts to provide feedback and follow up students. This paper examined the use of BL in higher education. The first part of this paper reviewed some empirical studies in BL. The second part presented the theoretical framework of using BL. Benefits and challenges of implementing BL in higher education regarding Saudi universities are explained. Lastly, the paper concluded with some critical remarks.